Analysis of breast milk fatty acid composition using dried milk samples. Issue 1 (December 2016) - Jackson, Kristina; Polreis, Jason; Sanborn, Laura; Chaima, David; Harris, William
Abstract Background The effect of breast milk fatty acid (FA) composition, particularly levels of docosahexaenoic acid (DHA), on infant health outcomes is unclear. Part of the reason for this is difficulties in collecting, storing and shipping milk samples to the laboratory. Here we report the validation of a dried milk spot (DMS) system to measure FA composition to help overcome these obstacles. Milk FA were measured by gas chromatography and reported as percent of total FA; the FA of primary interest in this study were DHA and industrially producedtrans FA (iTFA). Experiments were carried out using pooled milk samples from US (n  = 5) and Malawian women (n  = 50). Experiments compared liquid vs. DMS samples (n  = 55), assessed stability of FA composition under different storage conditions (n  = 5), and compared the results from two different labs using the same methods (n  = 5). Results Both % DHA and % iTFA levels in liquid and DMS samples were strongly correlated (R2  = 0.99 and 0.99, respectively, P  < 0.0001). The % DHA in DMS samples was stable for up to four weeks at room temperature and up to three years at -80 °C; only slight deviations from the acceptable range of variability (±15 %) occurred in the 4 °C and -20 °C conditions for % DHA. The % iTFA was stable under all conditions. All % DHA and % iTFA were within 15 % of the referent when analyzed in two laboratories. Conclusions Valid FA composition values can be obtained from DMS samples using this robust collection and transport system which should facilitate studies of the role of milk FA composition in infant development.